The Influence of Consumer Price Perceptions and Service Quality on Purchasing Decisions (Case Study of Traders at Kuto Ilir Timur Ii Market, Palembang) - Doly Nofiansyah; Riska Nurharita; Amir Salim; Saprida; Chandra Satria (Indonesian Journal of Advanced Research, 2024)
The purpose of this study was to find out how service quality and customer value perceptions influence purchasing decisions of traders at Pasar Kuto Ilir Timur II Palembang. The research method used is a quantitative method which is carried out through data collection, questionnaires, and field observations. The population of this study were traders and buyers in the kuto market and the sample in this study was 133 respondents. This study uses primary data derived from questionnaires with a Likert scale which are processed statistically through the SPSS version 25 program. Based on the research that has been done, the conclusion is that the variable service quality and perceived customer value are closely related to purchasing decisions. Furthermore, the results of the T hypothesis test which proves that there is an influence between service quality and customer value perceptions on purchasing decisions have been accepted because they have a Tcount score of 4,151 > Ttable 1.978 and a tcount of 4,917 > Ttable 1.978. Then the calculation of the coefficient of determination is 59.6%. The advice given is that considering the quality of service affects purchasing decisions, traders should continue to improve service quality by keeping the meat and fish vegetables sold clean, working well and fast and friendly in providing services so that consumers feel satisfied and their needs are fulfilled when shopping at Kuto Palembang Market.